Adsorption and desorption of self-assembled L-cysteine monolayers on nanoporous gold monitored by in situ resistometry - Hengge, Elisabeth; Steyskal, Eva-Maria; Bachler, Rupert; Dennig, Alexander; Nidetzky, Bernd; Würschum, Roland (Beilstein Journal of Nanotechnology, 2019)
Surface modifications of nanoporous metals have become a highly attractive research field as they exhibit great potential for various applications, especially in biotechnology. Using self-assembled monolayers is one of the most promising approaches to modify a gold surface. However, only few techniques are capable of characterizing the formation of these monolayers on porous substrates. Here, we present a method to in situ monitor the adsorption and desorption of self-assembled monolayers on nanoporous gold by resistometry, using cysteine as example. During the adsorption an overall relative change in resistance of 18% is detected, which occurs in three distinct stages. First, the cysteine molecules are adsorbed on the outer surface. In the second stage, they are adsorbed on the internal surfaces and in the last stage the reordering accompanied by additional adsorption takes place. The successful binding of cysteine on the Au surface was confirmed by cyclic voltammetry, which showed a significant decrease of the double-layer capacitance. Also, the electrochemically controlled desorption of cysteine was monitored by concomitant in situ resistometry. From the desorption peak related to the (111) surface of the structure, which is associated with a resistance change of 4.8%, an initial surface coverage of 0.48 monolayers of cysteine could be estimated.
Keywords: L-cysteine; in situ resistometry; nanoporous gold; self-assembled monolayer (SAM); voltammetry

(untitled) - Xiao, X.; Li, H.; Wang, M.; Zhang, K.; Si, P. (Analyst, 2014)

(untitled) - Meng, F.; Yan, X.; Liu, J.; Gu, J.; Zou, Z. (Electrochim. Acta, 2011)

(untitled) - Lang, X. Y.; Yuan, H. T.; Iwasa, Y.; Chen, M. W. (Scr. Mater., 2011)

(untitled) - Xiao, X.; Si, P.; Magner, E. (Bioelectrochemistry, 2016)

(untitled) - Mameka, N.; Lührs, L.; Heissler, S.; Gliemann, H.; Wöll, C. (ACS Appl. Nano Mater., 2018)

(untitled) - Vericat, C.; Vela, M. E.; Benitez, G.; Carro, P.; Salvarezza, R. C. (Chem. Soc. Rev., 2010)

(untitled) - Qingwen, L.; Hong, G.; Yiming, W.; Guoan, L.; Jie, M. (Electroanalysis, 2001)

(untitled) - Hakamada, M.; Takahashi, M.; Furukawa, T.; Tajima, K.; Yoshimura, K.; Chino, Y.; Mabuchi, M. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Steyskal, E.-M.; Qi, Z.; Pölt, P.; Albu, M.; Weissmüller, J.; Würschum, R. (Langmuir, 2016)

(untitled) - Jin, H.-J.; Parida, S.; Kramer, D.; Weissmüller, J. (Surf. Sci., 2008)

(untitled) - Hakamada, M.; Kato, N.; Mabuchi, M. (Appl. Surf. Sci., 2016)

(untitled) - Sumi, T.; Wano, H.; Uosaki, K. (J. Electroanal. Chem., 2003)

(untitled) - Torrelles, X.; Vericat, C.; Vela, M. E.; Fonticelli, M. H.; Daza Millone, M. A.; Felici, R.; Lee, T.-L.; Zegenhagen, J.; Muñoz, G.; Martín-Gago, J. A.; Salvarezza, R. C. (J. Phys. Chem. B, 2006)

(untitled) - Campuzano, S.; Pedrero, M.; Montemayor, C.; Fatás, E.; Pingarrón, J. M. (J. Electroanal. Chem., 2006)

(untitled) - Arihara, K.; Ariga, T.; Takashima, N.; Arihara, K.; Okajima, T.; Kitamura, F.; Tokuda, K.; Ohsaka, T. (Phys. Chem. Chem. Phys., 2003)

(untitled) - Huang, J.-F.; Sun, I.-W. (Adv. Funct. Mater., 2005)

(untitled) - Chu, Y.; Seo, B.-R.; Kim, J.-W. (Bull. Korean Chem. Soc., 2010)

(untitled) - Fawcett, W. R.; Fedurco, M.; Kováčová, Z.; Borkowska, Z. (J. Electroanal. Chem., 1994)

(untitled) - Wahl, P.; Traußnig, T.; Landgraf, S.; Jin, H.-J.; Weissmüller, J.; Würschum, R. (J. Appl. Phys., 2010)

(untitled) - Lakshmanan, C.; Viswanath, R.; Polaki, S.; Rajaraman, R. (AIP Conf. Proc., 2015)

(untitled) - Widrig, C. A.; Chung, C.; Porter, M. D. (J. Electroanal. Chem. Interfacial Electrochem., 1991)

(untitled) - Love, J. C.; Estroff, L. A.; Kriebel, J. K.; Nuzzo, R. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Cortés, E.; Rubert, A. A.; Benitez, G.; Carro, P.; Vela, M. E.; Salvarezza, R. C. (Langmuir, 2009)

(untitled) - Han, Y.; Uosaki, K. (Electrochim. Acta, 2008)

(untitled) - Kong, B.-K.; Kim, Y.-S.; Choi, I. S. (Bull. Korean Chem. Soc., 2008)